2017
DOI: 10.1073/pnas.1708568114
|View full text |Cite
|
Sign up to set email alerts
|

Lack of BACE1 S-palmitoylation reduces amyloid burden and mitigates memory deficits in transgenic mouse models of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a devastating neurodegenerative disorder characterized by pathological brain lesions and a decline in cognitive function. β-Amyloid peptides (Aβ), derived from proteolytic processing of amyloid precursor protein (APP), play a central role in AD pathogenesis. β-Site APP cleaving enzyme 1 (BACE1), the transmembrane aspartyl protease which initiates Aβ production, is axonally transported in neurons and accumulates in dystrophic neurites near cerebral amyloid deposits in AD. BACE1 is mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 70 publications
3
43
1
Order By: Relevance
“…Interestingly, the absence of S‐palmitoylation in BACE1 alleviates memory loss in Tg mice, to reveal the significant role of this PTM in localisation to specific compartments and amyloidogenesis. This study contradicts a few earlier reports (in vitro), but provides direct evidence in vivo …”
Section: Acylationcontrasting
confidence: 99%
“…Interestingly, the absence of S‐palmitoylation in BACE1 alleviates memory loss in Tg mice, to reveal the significant role of this PTM in localisation to specific compartments and amyloidogenesis. This study contradicts a few earlier reports (in vitro), but provides direct evidence in vivo …”
Section: Acylationcontrasting
confidence: 99%
“…For amyloid burden quantification (thioflavin S and mAb 3D6), five to eight sections per mouse were analyzed using ImageJ as described previously (58).…”
Section: Image Analysismentioning
confidence: 99%
“…The total number of arms entries (counted when all four limbs had entered the arm of the maze) and the sequence in which arms were entered were recorded. The percentage of spontaneous alternations was calculated and analyzed as described previously (58).…”
Section: Y-mazementioning
confidence: 99%
See 1 more Smart Citation
“…Other studies demonstrated that the palmitoylation of APP regulates its distribution in lipid rafts and its amyloidogenic processing (Bhattacharyya et al, 2013). The palmitoylation of BACE1 also regulates its enrichment in lipid rafts and although it does not affect its steady-state processing activity, it controls the synaptic activity-induced production of Ab (Vetrivel et al, 2009;Andrew et al, 2017).…”
Section: Biochemical Evidence Linking Cholesterol App and Its Cleavimentioning
confidence: 99%